A Cluster-Randomized, Controlled Trial of a Simplified Multifaceted Management Program for Individuals at High Cardiovascular Risk (SimCard Trial) in Rural Tibet, China, and Haryana, India. Issue 9 (1st September 2015) - Tian, Maoyi; Ajay, Vamadevan S.; Dunzhu, Danzeng; Hameed, Safraj S.; Li, Xian; Liu, Zhong; Li, Cong; Chen, Hao; Cho, KaWing; Li, Ruilai; Zhao, Xingshan; Jindal, Devraj; et al.
<x xml:space="preserve">Abstract</x> Background— In rural areas in China and India, the cardiovascular disease burden is high but economic and healthcare resources are limited. This study (the Simplified Cardiovascular Management Study [SimCard]) aims to develop and evaluate a simplified cardiovascular management program delivered by community health workers with the aid of a smartphone-based electronic decision support system. Methods and Results— The SimCard study was a yearlong cluster-randomized, controlled trial conducted in 47 villages (27 in China and 20 in India). Recruited for the study were 2086 individuals with high cardiovascular risk (aged ≥40 years with self-reported history of coronary heart disease, stroke, diabetes mellitus, and/or measured systolic blood pressure ≥160 mm Hg). Participants in the intervention villages were managed by community health workers through an Android-powered app on a monthly basis focusing on 2 medication use and 2 lifestyle modifications. In comparison with the control group, the intervention group had a 25.5% (P<0.001) higher net increase in the primary outcome of the proportion of patient-reported antihypertensive medication use pre- and post-intervention. There were also significant differences in certain secondary outcomes: aspirin use (net difference: 17.1%; P<0.001) and systolic blood pressure (–2.7 mm Hg; P=0.04). However, no significant changes were observed in the lifestyle factors. The intervention was culturally tailored, and country-specific results revealed important differences between the regions. Conclusions— The results indicate that the simplified cardiovascular management program improved quality of primary care and clinical outcomes in resource-poor settings in China and India. Larger trials in more places are needed to ascertain the potential impacts on mortality and morbidity outcomes. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT01503814.